RADIATION CHARACTERISTIC OF CLOUD BASED MAGNETOMETER FOR VEHICLE DETECTION - Yee, S. K.; Teoh, M. C.; Abidin, Z. Z.; Dahlan, S. H.; Anuar, M. R.; Tee, K. S.; Lim, D.; See, C. H.; Zhang, H.; Zheng, Y.; Soon, C. F. (2023)
A traffic sensing and monitoring system based on a magnetometer is proposed to work with Arduino pro-mini and nRF24L01 to mitigate traffic congestion problems. As vehicles pass through the magnetometer buried underground, the microcontroller processes the magnetic field changes and transmits them by the nRF24L01 transceiver for data analysis. A MIFA antenna resonating at 2.4 GHz is incorporated in the transceiver module for transmission purposes. The performance of this antenna is simulated by using COMSOL commercial software. Approximate 7 dB of return loss enhancement is found when taper design is applied to the antenna. Since the antenna is designed to radiate at 2.4 GHz, its antenna gain is the highest (1.22 dBi) in this frequency too. The simulated 3D and 2D gain patterns have shown that this antenna is radiating omnidirectional, suitable for transmitting signals in all directions. This is further validated by the Received Signal Strength Indicator (RSSI) measurement, which indicates a similar trend of signal strength for all locations at a distance below 40 m (-87 dBm). When the distances increase beyond 40 m, the RSSI at the direction closer to the traffic flow drops significantly compared to the other directions where 30 dBm of variation is detected at 100 m.